Behaviour and physiological response of Brahman cows reared in silvopastoral arrangements - Osorio-Giraldo, Jhon Fredy (2023)
The aim of this study was to evaluate the behaviour and physiological response of Brahman cows grazing in silvopastoral arrangements with scattered trees. The study was conducted in Puerto Nare, Antioquia, Colombia. Two productive systems were typified: a system with relevant shade cover with discontinuous trees and shrubs and a central alley of trees (protocol A) and a control system with scarce tree cover (protocol B). Each system included 19 Brahman cows with calves at foot. Lower environmental temperature was recorded in the paddocks of protocol A (p=0.04) and a higher respiratory rate in cows of protocol B (p=0.0001). There were no differences in dry matter intake (p=0.40), but there was more time dedicated to night grazing by cows from Protocol B (p=0.0017). It is concluded that silvopastoral systems with an adequate offer of shade allow to reduce the ambient temperature by up to 2°C, promoting welfare and comfort to Bos indicus cattle reared in tropical conditions.